The Global States and Hotspots of ERAS Research From 2000 to 2020: A Bibliometric and Visualized Study - Su, Shengjie; Wang, Tonghao; Wei, Ruiyuan; Jia, Xiaowu; Lin, Qiang; Bai, Minghua (Frontiers in Surgery, 2022)
Background: ERAS protocol has been implemented in surgeries for more than 20 years, this study investigated the global states and hotspots of enhanced recovery after surgery (ERAS) research. Methods: Based on the Web of Science database, a bibliometric analysis of original ERAS research from 2000 to 2020 was performed, including the trends of publications and citations; distribution of countries, authors, institutions, sources; study design, level of evidence, served surgeries and surgical disciplines. Hotspots were revealed by research interests and keywords. Results: Within the field of original ERAS research, there was a rising trend in annual publications and citations. The USA was the greatest contributor. Kehlet, H, University of Copenhagen were the most influential author and institution, respectively. British Journal of Surgery and Annals of Surgery were the most cited journals. Though there were more prospective designs, more than half of the studies presented level Ⅳ evidence and had fewer citations and citation densities compared to that of level Ⅱ and level Ⅲ. ERAS protocol was overwhelmingly implemented in colorectal surgeries. Most studies focused on elements of ERAS, the top three research interests were “length of stay”, “pain management”, and “complications”. In recent years, bariatric surgery, compliance with ERAS, and feasibility in the elderly were new hotspots. Conclusions: Revealing the global states and hotspots can help researchers better understand the trends in ERAS research. The USA was the greatest contributor to ERAS research. Kehlet, H, was the most influential author in the field. Bariatric surgery, compliance with ERAS, and feasibility in the elderly represent the new trend of ERAS research. Most of the ERAS research had a low evidence levels, studies with high-level evidence are still required in this field.